WAYS OF MODELING PROFESSIONAL ACTIVITY OF THE FUTURE TEACHER OF MUSIC MULTIMEDIA TEACHING MATERIALS (Pedagogy of Higher and Secondary Education, 2022)
In article mechanisms of modeling professional work of the future teacher of music are opened on the basis of laws multifunctional culture, functions of replacement that features asking the approach are found out during modeling professional work The essence of concepts "symesteticue" and "symestezhum" is debermined ways of use of metaphors are shined, opportunities of synthesis different are opened by a kind of arts. features of association scientific and art means knowledge of the world are analyzed.
Keywords: polyart preparation; multimedia means; modelling; model synesteticue; synestezium; the teacher of music